2022
DOI: 10.3390/life12050652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cannabidiol on Locomotor Activity

Abstract: Cannabidiol (CBD) is the second cannabinoid, in order of importance after Δ9-tetrahydrocannabinol (THC), from Cannabis sativa. Unlike THC, CBD does not cause psychotomimetic effects, and although these compounds have the same chemical formula, their pharmacological characteristics are not equivalent. Preclinical studies suggest that CBD has anti-inflammatory, analgesic, anxiolytic, antiemetic, anticonvulsant, and antipsychotic properties and influences the sleep–wake cycle. The evaluation of effects on spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 87 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…Besides chronic pain as a common comorbidity among PLWH, individuals also exhibit motor deficits, including impaired gait, multitasking, motor strength, and motor coordination, all correlated with HAND status ( Schleicher et al, 2019 ; Florensa-Zanuy et al, 2021 ). As a result of these motor difficulties, physical activity often suffers, and a majority of PLWH exhibit inadequate levels of daily physical activity, even lower than most other chronic disease populations ( Calapai et al, 2022 ). These lower levels of activity have been associated with depression, physical pain, and worse cardio-respiratory fitness ( Magen et al, 2010 ; Calapai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides chronic pain as a common comorbidity among PLWH, individuals also exhibit motor deficits, including impaired gait, multitasking, motor strength, and motor coordination, all correlated with HAND status ( Schleicher et al, 2019 ; Florensa-Zanuy et al, 2021 ). As a result of these motor difficulties, physical activity often suffers, and a majority of PLWH exhibit inadequate levels of daily physical activity, even lower than most other chronic disease populations ( Calapai et al, 2022 ). These lower levels of activity have been associated with depression, physical pain, and worse cardio-respiratory fitness ( Magen et al, 2010 ; Calapai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that other studies report no effect at low doses or an increase or a decrease in locomotor activity after high doses in mice [ 55 , 56 ]. Whereas rats treated with CBD show hyperlocomotive effects after 10 and 30 mg/kg but only after 240–360 min post-administration [ 50 , 57 ]. Thus, CBD's action on locomotor activity seems to depend on experimental settings and species, and probably reflects the activation of distinct pathways in the different settings, as if CBD was at the crossroads of multiple circuits.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies showing that CBD can block the effects of MK‐801 (Kruk‐Slomka & Biala, 2021). While CBD or CBDA alone does not seem to affect locomotor activity (Calapai et al, 2022), its regulation of NDMAR via CB1Rs and 5‐HT1ARs is likely one of the mechanisms that reverses MK‐801‐indcued hyperlocomotion (Rodríguez‐Muñoz et al, 2016; Yuen et al, 2005). Previous research showed that NMDAR antagonism can induce immobility in the FST (Langen et al, 2012), and our study corroborates the findings that compounds such as CBD and HU‐580 can significantly reduce immobility behaviour (Dlugosz et al, 2023; Sales et al, 2019, 2020).…”
Section: Discussionmentioning
confidence: 99%